Characterization of the Escherichia coli Antifungal Protein PPEBL21 - V. Yadav; R. Mandhan; M. Kumar; J. Gupta; G. L. Sharma (International Journal of Microbiology)
An antifungal protein isolated from Escherichia coli BL21 (PPEBL21) and predicted to be alcohol dehydrogenase (ADH) was subjected to biological characterization. The PPEBL21, indeed, demonstrated propionaldehyde-specific ADH activity. The Km and Vmax of PPEBL21 were found to be 644.8 μM and 1.2 U/mg, respectively. In-gel activity assay also showed that PPEBL21 was a propionaldehyde-specific ADH. The pI of PPEBL21 was observed to be 7.8. PPEBL21 was found to be stable up to a temperature of 40∘C with optimum activity at pH 7.5. The decrease in pH decreased the activity of PPEBL21. These results suggested that PPEBL21 having alcohol dehydrogenase activity and stability at significantly high temperature might be an important lead antifungal molecule. Experiments were performed to identify the possible target of PPEBL21 in the pathogen A. fumigatus. Results revealed that PPEBL21 inhibited completely the expression of a 16 kDa protein in A. fumigatus. The 16 kDa protein of A. fumigatus targeted by PPEBL21 was identified as a hypothetical protein by peptide mass fingerprinting. It is thus hypothesized that a 16 kDa factor is essentially required by A. fumigatus for survival and its impaired synthesis due to treatment with PPEBL21 may lead to the death of pathogen.